Slovenska podjetja in značilnosti start-up ekosistema: Slovenski podjetniški observatorij 2015 - Močnik, Dijana; Rus, Matej (University of Maribor Press, 2016)
Slovenian Companies and Characteristics of Start-up Ecosystem : Slovenian Entrepreneurship Observatory 2015. In this monograph, we first analysed all companies and entrepreneurs in Slovenia in 2014; then, for 2012, we compared the critical data for companies from the EU-28 and Slovenia in the non-financial business sector (activities of industry, trade and services). In Slovenia in 2014, 63,590 companies (almost 4% more than in the previous year) and 67,500 entrepreneurs (3% less than the previous year) − totalling 131,090 enterprises − employed more than 526,000 people. More than one quarter of enterprises in the non-financial business sector in the EU-28 in 2012 operated in distributive trades (motor trades, wholesale trade and retail trade). This activity also employed the most people (i.e., one quarter). In order to learn more about Slovenian start-up companies, the start-up ecosystem and the key challenges for improvements, we analysed the characteristics of Slovenian start-up companies and the start-up ecosystem. We employed primary data from 156 start-up companies, whose average age was 2.1 years, included in the research study.